Some Thoughts on Macroeconomic Fluctuations and the Timing of Labor Market Reform - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2002)
n this paper, I analyze the pros and cons of implementing structural reforms of the labor market in booms vs. recessions, in light of considerations of social efficiency, political viability, and macroeconomic fine tuning. While the optimal timing of a reform depends on the relative importance of several conflicting effects, it seems clear that a reform should be accompanied by an expansionary macroeconomic policy. This makes structural reform more problematic in the context of the European Monetary Union.
Keywords: K31; J6; E61; E52; E32; 330; labour market reforms; unemployment; employment protection; monetary union; firing costs; political economy; Arbeitsmarktflexibilisierung; Reform; Konjunktur; Public Choice; Europäische Wirtschafts- und Währungsunion